A production type-curve solution for coalbed methane reservoirs. (March 2015) - Thararoop, Prob; Karpyn, Zuleima T.; Ertekin, Turgay
Abstract: A production type-curve solution for coalbed methane reservoirs is presented in this paper. The proposed production type curves were generated in terms of dimensionless production rate and dimensionless time groups that are based on the diffusivity equations of the two-phase flow in dual-porosity, dual-permeability coalbed methane reservoirs. The dual-porosity, dual-permeability reservoir simulation model is used as a tool in constructing the production type curves with constant sandface pressure specifications at the inner boundary. Sensitivity analyses are performed to investigate the capability of the proposed production type curves. Several sets of type-curve matching exercises are successfully performed to predict reservoir properties on different systems exhibiting a variety of reservoir and fluid properties. The proposed production type curves can be used to estimate reservoir properties including fracture permeability, fracture porosity, matrix porosity and water saturations in the fracture and matrix systems.